2023
DOI: 10.1063/5.0139443
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin–orbit torque in Pt/Co/HfOx heterostructures with voltage-controlled oxygen ion migration

Abstract: Spin–orbit torque (SOT) induced magnetization switching and SOT modulation by interfacial coupling exhibit good potential in spintronic devices. In this work, we report the enhancement of damping-like field and SOT efficiency of up to 60% and 23%, respectively, in perpendicularly magnetized Pt/Co/HfOx heterostructures over a Pt/Co system at an optimal thickness of 2 nm HfOx. The SOT improvement is primarily attributed to the interfacial oxidization of the Co layer, and the strength is tunable via voltage-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Recently, Yang et al reported the field-free magnetization switching by PtTe 2 /WTe 2 with very high spin Hall conductivity . Meanwhile, various methods have been explored to improve the efficiency of SOT, such as light modulation, electric field modulation, and alloying. There have been extensive studies on methods to increase the magnitude of the spin Hall angle by adding nonmagnetic impurities to heavy metal materials, such as Pt doped with Au, Bi, Cu, and Pd .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al reported the field-free magnetization switching by PtTe 2 /WTe 2 with very high spin Hall conductivity . Meanwhile, various methods have been explored to improve the efficiency of SOT, such as light modulation, electric field modulation, and alloying. There have been extensive studies on methods to increase the magnitude of the spin Hall angle by adding nonmagnetic impurities to heavy metal materials, such as Pt doped with Au, Bi, Cu, and Pd .…”
Section: Introductionmentioning
confidence: 99%
“…This gate-voltage-induced oxidation process offers a promising way to manipulate interfacial properties and, consequently, modulate SOT efficiency in a controllable and reversible manner. Notably, voltage control of SOT has been demonstrated in various systems, such as the Pt/Co system [20,21], a Crdoped topological insulator [22], and using ionic liquid [12,23]. Previous works [24][25][26] primarily utilized electric fields to influence interfacial oxidation in voltage-controlled magnetism within ferromagnetic/oxide systems, thereby facilitating magnetization switching through changes in magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the Pt/Co/Ti sample, a pulsed field of −40 Oe is applied, resulting in the nucleation of a dark domain at one boundary, which subsequently grows larger with the continuous application of the same pulsed field. The DW motion leads to the sharp switching as observed in the M – H oop loop in the Pt/Co/Ti sample. However, granular magnetization switching is observed in the Pt/Co/HfOx/Ti sample, as revealed by Kerr imaging. The number of nucleated dark domains rapidly increases with the continuous application of the pulsed field instead of undergoing magnetization reversal via DW motion.…”
mentioning
confidence: 99%
“…In both cases, H DL with J ac exhibits good linearity. 31 To comprise the SOT efficiency, the damping-like field efficiency χ of two stacks is extracted, where χ is defined as H DL /J ac . The χ DL increases from 9.1 to 11.5 Oe/(10 10 A/m 2 ) with the addition of the HfOx insertion layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation